2007
DOI: 10.1111/j.1365-2265.2007.02966.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating visfatin level is correlated with inflammation, but not with insulin resistance

Abstract: Serum visfatin levels were positively correlated with the serum levels of IL-6 and slightly related with serum levels of CRP, but not with HOMA-IR, in Japanese Americans. Our results indicate that circulating visfatin may reflect inflammation status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
75
4
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 25 publications
9
75
4
7
Order By: Relevance
“…However, more recent in vivo and in vitro studies have suggested that visfatin may be related to insulin-resistance, endothelial dysfunction, and increased inflammation. [3][4][5][6] Despite these findings, it should be noted that comprehensive results do not yet exist about the pathophysiological role of visfatin. [4] Dialysis patients are suggested to have increased several adipocytokines (adiponectin, leptin, interleukin 6 [IL-6], tumor necrosis factor-α [TNF-α]), particularly due to low renal clearance.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…However, more recent in vivo and in vitro studies have suggested that visfatin may be related to insulin-resistance, endothelial dysfunction, and increased inflammation. [3][4][5][6] Despite these findings, it should be noted that comprehensive results do not yet exist about the pathophysiological role of visfatin. [4] Dialysis patients are suggested to have increased several adipocytokines (adiponectin, leptin, interleukin 6 [IL-6], tumor necrosis factor-α [TNF-α]), particularly due to low renal clearance.…”
Section: Introductionmentioning
confidence: 83%
“…[1,4,5] Additionally, a few studies have suggested that visfatin may have proinflammatory characteristics. [3,4,6] There are two studies in the literature demonstrating a positive relationship between serum level of IL-6 and visfatin. [3,6] Likewise, our study has also found an independent and significant positive relationship between visfatin and two of the important inflammatory cytokines, TNF-α and IL-6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this Japanese American population-based study, the subjects have been reported to develop dyslipidaemia and obesity more rapidly than Japanese living in Japan because of a Westernised food habit in which Japanese Americans ingested more fat of animal origin and of a lower PUFA:SFA ratio than native Japanese (7,8) . Therefore, we considered that these populations * Corresponding author: Dr Kiminori Yamane, fax þ81 82 255 7360, email yamanek@hiroshima-u.ac.jp Abbreviations: %fat, percentage body fat; HMG, 3-hydroxy-3-methylglutaryl; HOMA-IR, homeostasis model assessment for insulin resistance; SNP, single nucleotide polymorphism.…”
mentioning
confidence: 99%